Addictions : a banquet in the grave : finding hope in the power of the Gospel - Welch, Edward T., 1953- (Phillipsburg, New Jersey : P and R Pub., 2001)
A worship disorder: this is how Edward T. Welch views addictions. "Will we worship our own desires or will we worship the true God?" With this lens the author discovers far more in Scripture on addictions than passages on drunkenness. There we learn the addict's true condition: like guests at a banquet thrown by "the woman Folly," he is already in the grave (Proverbs 9:13-18). Can we not escape our addictions? If we're willing to follow Jesus, the author says that we have "immense hope: hope in God's forgiving grace, hope in God's love that is faithful even when we are not, and hope that God can give power so that we are no longer mastered by the addiction." Each chapter concludes with "Practical Theology," "As Your Face Your Own Addictions," and "As You Help Someone Else."
PART 1: THINKING THEOLOGICALLY Practical theology Sin, sickness, or both? New ways of seeing Descent into addiction. PART 2: ESSENTIAL THEOLOGICAL THEMES Speaking the truth in love Respecting, listening, and inviting Knowing the Lord Fearing the Lord Turning from lies Saying "No" Staying violent Being part of the body Conclusion: where two or three are gathered.
Includes bibliographical references (pages 291-293) and index.
2
2
Ed, M.Div., Ph.D. is a counselor and faculty member at CCEF where he has served for more than 35 years. He earned a Ph.D. in counseling (neuropsychology) from the University of Utah and has a Master of Divinity degree from Biblical Theological Seminary. Ed has been counseling for over thirty years and has written many books and articles on biblical counseling, including When People Are Big and God Is Small; Addictions: A Banquet in the Grave; Blame It on the Brain?; Depression; Running Scared; Shame, Interrupted; and Side by Side: Walking with Others in Wisdom and Love. He and his wife, Sheri, have two married daughters and eight grandchildren. In his spare time, Ed enjoys spending time with his wife and extended family and playing his guitar.
Keywords: Addicts -- Religious life; Alcoholics -- Religious life; Christian Counseling